Palisaded Neutrophilic Granulomatous Dermatitis in a Patient with Systemic Sclerosis-Rheumatoid Arthritis Overlap Syndrome - Jung, Kyong-Hee; Jeong, Sangho; Kwon, Seong-Ryul; Lim, Mie Jin; Gwon, Jiyeon; Shin, Jeonghyun; Park, Won (Annals of dermatology, 2017)
KCI Citation Count: 1